where \frac{\Delta Y}{Y} = GDP percentage growth \frac{\Delta A}{A} = percentage growth from total factor productivity (TFP) \frac{\Delta K}{K} = percentage growth in capital \frac{\Delta L}{L} = percentage growth in labor \alpha = share of income paid to capital factor 1-\alpha = share of income paid to labor factor
TFP = Labor productivity growth - Growth in capital deepening,
If we assume
(i) \alpha=0 so all income is paid to labor factor
and (ii) there is no capital deepening,so that TFP = Labor productivity growth,
then \frac{\Delta A}{A} = percentage growth from labour productivity
\frac{\Delta Y}{Y}= percentage growth from labor productivity +\frac{\Delta L}{L}
which answers @FrankCFA 's question from 10 years ago about how to derive the first equation from the second